TINJAUAN FIQH SIYASAH TERHADAP IMPLEMENTASI VISI DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DALAM MEWUJUDKAN PEMERINTAH PROVINSI LAMPUNG YANG ASPIRATIF - reza maharani; fathul mu'in; nur rahmah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the implementation of the vision of the Regional Representative Council of the Republic of Indonesia in realizing an aspirational Lampung Provincial Government using the perspective of Fiqh Siyasah. The background of this research is based on the importance of the role of DPD as a regional representative institution in channeling and fighting for the aspirations of the community, especially in the context of participatory and responsive absorption and delivery of aspirations. This research uses a qualitative method with a juridical-normative approach and is supported by relevant literature studies. The focus of the study is directed at the extent to which the implementation of the DPD's vision has reflected the basic principles of fiqh siyasah, such as shura (deliberation), amanah (responsibility), and maslahah (public good). The results of the study show that the implementation of the DPD's vision in realizing an aspirational government in Lampung Province has not been fully optimal. This situation can be seen from the limited effectiveness of absorbing people's aspirations, the lack of synergy between institutions, and the lack of maximum public participation. Based on the perspective of fiqh siyasah, this condition shows a lack of conformity with the principles of ideal governance. Therefore, it is necessary to strengthen the role of the DPD, increase community participation, and optimize the mechanism for distributing aspirations to realize a more aspirational and benefit-oriented government.